PROFILE OF DYSPHAGIA IN ACUTE STROKE PATIENTS - Rakhmatiar, Rodhiyan; Dwirima, Wahyu (MNJ (Malang Neurology Journal), 2024)
Background: Stroke has been a leading cause of mortality and disability since 2013, and its incidence continues to rise. Dysphagia is a common complication following stroke, contributing to increased rates of aspiration, pneumonia, and prolonged hospital stays for stroke patients. Objective: This study aims to investigate the profile and distribution of acute stroke patients experiencing dysphagia who are admitted to RSUD dr. Saiful Anwar in East Java. Methods: The assessment was conducted on acute stroke patients with compos mentis consciousness in the Stroke Unit from July to September 2023, using the GUSS (Gugging Swallowing Screen) questionnaire. The assessment categories included no dysphagia (20), mild dysphagia (15-19), moderate dysphagia (10-14), and severe dysphagia (0-9). Results: Data collected during the period from July to September 2023 yielded a total of 35 samples. Based on gender, there were 22 male patients (62.9%) and 13 female patients (37.1%). Regarding age distribution, 15 patients fell into the productive age range (20 to 59 years), while 20 patients were over 60 years old. The majority of cases were ischemic strokes, with 25 patients, and 10 patients had hemorrhagic strokes. Dysphagia assessment using the GUSS method on the 35 samples revealed 2 samples with GUSS scores of 12 and 14 (moderate) and 1 sample with a score of 18 (mild). Conclusion: The profile and distribution of acute stroke patients experiencing dysphagia were identified, including gender, age, type of stroke, and GUSS scores in acute stroke patients in the stroke unit with Compos Mentis consciousness.